2021
DOI: 10.1039/d0cp06460b
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric response of light, heavy and heavy-oxygen water: isotope effects on the hydrogen-bonding network's collective relaxation dynamics

Abstract: Isotopic substitutions largely affect the dielectric relaxation dynamics of hydrogen-bonded liquid water; yet, the role of the altered molecular masses and nuclear quantum effects has not been fully established. To...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…For comparison with the present results (that are based on measurements of dynamic rather than thermodynamic quantities) it is reassuring that also kinetic observables such as the (zero-frequency) viscosity, 66 the dielectric microwave absorption, 14 and even responses in the terahertz and infrared regimes of liquid water and aqueous solutions show the same trends regarding the isotope shifts. 67,68…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…For comparison with the present results (that are based on measurements of dynamic rather than thermodynamic quantities) it is reassuring that also kinetic observables such as the (zero-frequency) viscosity, 66 the dielectric microwave absorption, 14 and even responses in the terahertz and infrared regimes of liquid water and aqueous solutions show the same trends regarding the isotope shifts. 67,68…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our findings vindicate the statement expressed in view of ref. 14 that “Recently, the central role of translational diffusion for dielectric relaxation was explicitly demonstrated by studying isotope effects on the dielectric relaxation spectra.” 63…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Shinde et al used an estimation of the average number of H-bonds in combinations of 1,3-propandiol and 1,4-dioxane to explain the dielectric constant behavior of their mixtures, 19 and a recent study by Kutus et al explored how differences in H-bonding interactions found in isotopes of water (H 2 16 O, D 2 16 O, and H 2 18 O) result in variation of their dielectric relaxation spectra. 20 In 2018, a study exploring the isopermitive frequency (IPF, defined as the frequency at which the relative permittivity of water is almost independent of temperature) investigated how the presence of ions (using NaCl/MgCl 2 ) can alter the Hbonding networks in water. This low-frequency technique (1− 40 MHz) obtained qualitative information about the H-bond networks in water solutions and their rearrangements.…”
Section: Introductionmentioning
confidence: 99%